Learning from authoritarian teachers: Controlling the situation or controlling yourself can sustain motivation - Chaffee, Kathryn E.; Noels, Kimberly A.; McEown, Maya Sugita (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2014)
Positive psychology encompasses the study of positive outcomes, optimal functioning, and resilience in difficult circumstances. In the context of language learning, positive outcomes include academic engagement, self-determined motivation, persistence in language learning, and eventually becoming a proficient user of the language. These questionnaire studies extend previous research by addressing how these positive outcomes can be achieved even in adverse circumstances. In Study 1, the primary and secondary control scales of interest were validated using 2468 students at a Canadian university. Study 2 examined the capacity of 100 Ca- nadian language learners to adjust themselves to fit in with their environment, termed secondary control, and how it was related to their motivation for and engagement in language learning and their feelings of anxiety speaking in the class- room. Secondary control in the form of adjusting one’s attitude towards language learning challenges through positive reappraisals was positively associated with self-determined motivation, need satisfaction, and engagement. In regression analyses, positive reappraisals were also found to buffer the negative effects of having a controlling instructor on students’ engagement and anxiety. These find- ings suggest that personal characteristics interact with the learning environment to allow students to function optimally in their language courses even when the teacher is controlling.
Keywords: primary control; secondary control; positive reappraisal; motivation; controlling instructor